Metagenomics of polycylic aromatic hydrocarbon (PAH) contaminated soil - Mohd Ashaari, Mardiana; Hutchens, Elena; Murphy, Ciara; Clipson, Nicholas; Doyle, Evelyn (2010)
Release of contaminants such as polycyclic aromatic hydrocarbons (PAHs) into the environment both naturally and anthropogenically, through forest fires, incomplete combustion of fossil fuels, petroleum product spills, manufacture of coke and wood preservation using creosote is a major cause of pollution. PAHs are not only a threat to the environment but some of the compounds are also mutagenic and carcinogenic to humans. Bioremediation has great potential to clean up PAH contaminated sites, provided that both the physico-chemical characteristics of the contaminated site and the microbial communities involved in key physiological processes are fully understood. The aim of this study was to analyse genetic material of the entire microbial community present in PAH contaminated soil using a metagenomic approach.